The Influence of The Project Based Learning (PjBL) Learning Model on Students' Spatial Thinking Abilities on The Subject of Geography - Ristiani, Ristiani (Indo-MathEdu Intellectuals Journal, 2025)
Geography is one of the important subjects in the education curriculum in Indonesia. The ability to think spatially is one of the important skills that students must master in learning geography. Teachers need to apply appropriate learning models to train students' spatial thinking skills, such as project-based learning models. This research uses a literature review method of 9 (nine) articles to analyze the influence of the project based learning model on students' spatial thinking abilities in geography subjects. The source of data for this research is scientific articles published in various journals and indexed in the google scholar repository data. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the project based learning model has a significant influence on students' spatial thinking abilities in geography subjects. The application of the PjBL learning model has been proven to improve students' spatial thinking skills which are needed in studying spatial concepts in geography.